Molecular characterisation of TP53 mutated squamous cell carcinomas of the lung to identify putative targets for therapy. Issue 10 (17th June 2020) - Haakensen, Vilde D.; Khadse, Anand; Sandhu, Vandana; Halvorsen, Ann Rita; Solberg, Steinar K.; Jørgensen, Lars H.; Brustugun, Odd Terje; Kure, Elin H.; Helland, Åslaug
Abstract: Personalised cancer treatment depends on identification of therapeutically relevant biological subgroups of patients for assessing effect of treatment and to discover new therapeutic options. By analyses in heterogeneous patient populations, the effects may be lost in noise. Squamous cell carcinoma of the lung is a major killer worldwide. Despite recent advances, mortality is high and response to therapies varies greatly from patient to patient. Target search in biologically relevant subgroups may identify treatment options not so far discovered. A total of 198 patients undergoing surgery for squamous cell carcinomas of the lung were included in the study. The tumours were analysed for copy number alterations (n = 152) and gene expression from tumour (n = 188) and normal lung (n = 21), with both data levels present in 140 patients. We studied alterations in tumours harbouring mutations in TP53 and in previously published gene expression subtypes. Genes with consistent alterations in both genomic levels were identified as putative biomarkers. Results were validated in TCGA. The most convincing biomarker in TP53 mutated squamous cell carcinomas of the lung was BIRC5 with amplification in 36% of mutated samples, 5% in wild‐type samples and a 17%‐fold change of expression between TP53 mutated tumours and normal lung tissue. BIRC5 was significantly altered in the classical and primitive subtypes. We suggest BIRC5 as a putative predictive biomarker and putative druggable target in squamous cell lung carcinomas harbouring TP53 mutation or classified as classical and primitive subtypes. Abstract : What's new? This study presents a target gene search combining copy number alteration and gene expression to identify putative genes for therapeutic and predictive approaches in TP53 mutated lung squamous cell carcinoma (SCC) and published gene expression subtypes with high percentages of TP53 mutations. Several potential biomarkers and therapeutic targets emerged from these pre‐defined biological subgroups. The results suggest that BIRC5 is one of the most appealing targets in TP53 mutated cancers and in the classical and primitive subtypes and should be tested clinically in these subgroups. Testing in biologically defined subgroups may increase likelihood of discovering clinically relevant treatment effects.